Target therapy for BRAF mutated anaplastic thyroid cancer: a clinical and molecular study. Issue 1 (10th January 2023) - da Silva, Tiago Nunes; Rodrigues, Ricardo; Saramago, Ana; Pires, Carolina; Rito, Miguel; Horta, Mariana; Martins, Carmo; Leite, Valeriano; Cavaco, Branca M
Abstract: Objectives: Anaplastic thyroid carcinoma (ATC) has a poor survival. The combination of Dabrafenib plus Trametinib (DT) had a significant impact in survival of BRAF p.V600E patients. However, durable responses may be compromised by resistance. We aim to present our experience with DT in BRAF positive ATC patients and compare the outcomes with usual therapy, and to study tumor molecular alterations in the DT group. Methods: Patients treated between May 2018 and April 2022 in a tertiary referral center, assessed for BRAF status were included. Patients were divided in three groups: BRAF p.V600E treated with DT, BRAF wild type (WT) under multimodal therapy (MT), and BRAF WT under compassionate care (CC). Response was assessed monthly in the first 6 months and every 3 months afterwards, by RECIST 1.1. Overall survival (OS) and progression-free survival (PFS) were estimated with the Kaplan-Meier method and compared with the log-rank test. Results: Twenty-seven ATC patients were included (DT = 9, MT = 8, and CC = 10). Median OS was 475 days for DT, 156 days for MT, and 39 days for CC ( P < .001). At 12 months, only patients in the DT group were alive (71%). Median PFS was 270 days, in the DT group, compared with less than 32 days in BRAF WT ( P < .001). No severe adverse events were reported. Molecular profiling showed that in one of the four clinical progressions, a pathogenic NRAS mutation was found. Conclusions: Our results show a significant real-world efficacy of Dabrafenib plus Trametinib in both survival and recurrence compared with standard treatment, with a good safety profile.